2003
DOI: 10.1016/j.hep.2003.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants of the chemokine receptor CCR5 and its ligands, RANTES and MCP-2, with outcome of HCV infection

Abstract: The effect of host genetic variation on the outcome of hepatitis C virus (HCV) infection and its treatment is poorly understood. The chemokine receptors CCR5, CCR2, and CCR3 and their ligands, RANTES, MCP-1, MCP-2, and MIP-1␣, are involved in the immune responses and the selective recruitment of lymphocytes to the liver in HCV infection. We studied 20 polymorphisms within these genes and investigated their association with persistent carriage of HCV, severity of liver disease, hepatic inflammation, and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 41 publications
5
93
1
2
Order By: Relevance
“…For example, several CC chemokine polymorphisms have been associated with susceptibility to HCV and disease progression, including the gene for RANTES and its receptor CCR5, and MCP-1 (Woitas et al, 2002;Hellier et al, 2003;Muhlbauer et al, 2003). Hellier et al (2003) identified a polymorphism at position -403 in the RANTES gene promoter and in the CCR5 32 allele that was associated with reduced hepatic portal inflammation. Furthermore, the −403 RANTES polymorphism appears to be functional with the −403A allele leading to increased transcription of RANTES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several CC chemokine polymorphisms have been associated with susceptibility to HCV and disease progression, including the gene for RANTES and its receptor CCR5, and MCP-1 (Woitas et al, 2002;Hellier et al, 2003;Muhlbauer et al, 2003). Hellier et al (2003) identified a polymorphism at position -403 in the RANTES gene promoter and in the CCR5 32 allele that was associated with reduced hepatic portal inflammation. Furthermore, the −403 RANTES polymorphism appears to be functional with the −403A allele leading to increased transcription of RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of T cells within the HCV infected liver are known to preferentially express the chemokine receptors CCR5 and CXCR3 (Shields et al, 1999 andHarvey et al, 2003), suggesting that the CC and CXC chemokines play an important role in the inflammatory process of the HCV infected liver. Several CC chemokine polymorphisms have been associated with susceptibility to HCV and disease progression, including the CCR5 32, RANTES −403A and MCP-1 −2518G polymorphic variants (Woitas et al, 2002;Hellier et al, 2003;Muhlbauer et al, 2003). However, to our knowledge no polymorphic variants in the CXCR3 family of chemokines have been identified to play a functional role in chronic HCV.…”
Section: Introductionmentioning
confidence: 95%
“…and CCR3 [25] and reported four main findings: (i) the CCR5 32 allele is associated with mild fibrosis and reduced portal inflammation; (ii) polymorphisms in a CCR5 promoter-the 2132-C allele-are associated with increased risk of HCV persistence and with better initial response to interferon; (iii) the CCL5-403 promoter polymorphism is associated with portal inflammation; and (iv) the MCP-2 Q46K mutation is associated with more severe fibrosis. The British study by Goulding et al [26] confirmed the protective role of the CCR5 32 allele in HCV, but a Spanish study [27] reached the opposite conclusion, finding the frequency of the CCR5 32 allele did not differ between case and control groups.…”
Section: Hcvmentioning
confidence: 99%
“…In contrast, in naïve European rabbit, this large DNA virus causes a systemic immune deficiency with a fatal outcome (reviewed in Abrantes et al 2012;Spiesschaert et al 2011). Numerous studies have documented the crucial role played by CCL8 and its posttranslational byproducts in CCR5-dependent signal transduction (Hellier et al 2003;Loetscher et al 1994;Struyf et al 2009), more in particular in Human during infection by HIV (Moser et al 2004;Proost et al 1998a, b).…”
Section: Introductionmentioning
confidence: 99%